Corneal allogeneic intrastromal ring segments (CAIRS): the New Kid on the Block = Korneale allogene intrastromale Ringsegmente (CAIRS): The New Kid on the Block - Son, Hyeck Soo; Augustin, Victor A.; Friedrich, Maximilian; Yildirim, Timur Mert; Khoramnia, Ramin; Auffarth, Gerd U. (Klinische Monatsblätter für Augenheilkunde, 2025)
Corneal allogeneic intrastromal ring segments (CAIRS) have recently been introduced as a novel therapeutic modality for keratoconus and corneal ectatic conditions. As with synthetic intracorneal segments, CAIRS are transplanted into intrastromal channel created via femtosecond laser, in order to regularise the corneal geometry, reduce myopia and astigmatism as well as higher-order aberrations, thus ultimately improving visual and topographic parameters. A growing body of clinical evidence supports the efficacy and safety of this approach, and CAIRS has thus become a paradigm shift in keratoconus treatment. This article provides a brief overview of CAIRS, its surgical indication, and graft preparation and possible customisation.